Characterization of tyrosine hydroxylase from Manduca sexta - Gorman, Maureen J. (2007)
In insects, 3,4-dihydroxyphenylalanine (DOPA) is required for tanning of newly formed cuticle and the production of melanin during some types of immune responses. DOPA is produced by the hydroxylation of tyrosine, and this reaction can be catalyzed by two types of enzymes: tyrosine hydroxylase (TH) and phenoloxidase (PO). TH is required for cuticle tanning in Drosophila melanogaster and for cuticle pigmentation in other insect species, but additional functions of TH have been uncertain. In contrast, an immune function for PO has been well documented. The goal of this study was to characterize TH from Manduca sexta with a focus on its possible contribution to cuticle tanning and immune-associated melanization. We cloned a full length TH cDNA, purified recombinant TH, and confirmed that MsTH and MsPO have tyrosine hydroxylating activity. To determine possible functions, we analyzed TH expression profiles. TH mRNA and protein were present in eggs at the stage when the pharate larval cuticle begins to tan and also in the integument of molting larvae. The amount of TH in the integument was correlated with the degree of cuticle tanning. Unlike PO, which was found to be constitutively expressed by hemocytes and was present in plasma, TH was upregulated in hemocytes and the fat body in response to an immune challenge and remained intracellular. These data suggest that TH is required for cuticle tanning and immunity in M. sexta. Based on the collective information from many studies, we propose a model in which TH is a major producer of the DOPA required for both cuticle tanning and immune-associated melanization.